Clinical features, prognostic factors, and survival of patients with antisynthetase syndrome and interstitial lung disease - Zhao, Na; Jiang, Wei; Wu, Hongliang; Wang, Ping; Wang, Xiaoni; Bai, Yu; Li, Yao; Tang, Yanchun; Liu, Ying (Frontiers in Immunology, 2022)
Abstract Objective This study aimed to analyze the clinical features and prognostic factors of imaging progression and survival in patients with antisynthetase syndrome (ASS) complicated by interstitial lung disease (ILD) in a large Chinese cohort. Methods Medical records, imaging, and serological data of 111 patients with ASS-ILD (positive for at least one of the following autoantibodies: anti-Jo1, anti-PL7, anti-PL12, and anti-EJ) from the Affiliated Yantai Yuhuangding Hospital of Qingdao University database were retrospectively investigated. According to the changes in high-resolution computed tomography (HRCT) outcomes at 1 year follow-up, Patients were categorized into three groups: the regression, stability, and deterioration groups. Univariate analysis was performed to evaluate the possible prognostic factors of ILD outcome and death, and multivariate analysis was performed to determine the independent predictors of ASS-ILD outcome and death by logistic regression. Results The number of CD3-CD19+ cells and initial glucocorticoid dosage were correlated with imaging progression, and may be independent risk factors for ILD deterioration. Dyspnea as the first symptom, hypohemoglobinemia, the serum ferritin level, oxygen partial pressure at diagnosis, and different treatment types were important factors affecting survival, and the initial serum ferritin level may be an independent risk factor for survival. Conclusions The clinical characteristics of patients with ASS-ILD with different antisynthetase antibody subtypes are different. An increase in the CD3-CD19+ cell level is an independent risk factor for the deterioration of HRCT imaging. Early intensive treatment with high-dose glucocorticoids can effectively improve imaging prognosis of ILD. Patients with significantly elevated serum ferritin levels should be treated intensively. Keywords: interstitial lung disease; antisynthetase syndrome; prognostic factors; Clinical features; survival factors